The Impact of Halal Tourism to the Income and Welfare of the Local People of Makassar - Wahyuni, Sinar; Deflyanty. S, Putri; Muslihati; Sri Wahyuni Safitri (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
Recognizing halal tourism’s significant potential for regional economic enhancement, this study investigates its socio-economic impact on local residents in Makassar City. Objectives: The research aims to determine the influence of halal tourism on local community income and assess its subsequent effect on community welfare within Makassar City. Method: Employing a quantitative approach, the study utilized stratified random sampling to select 100 engaged local respondents, derived using the Slovin formula (10% error). Data analysis was executed via SEM Smart-PLS. Main Results and Implications: The main findings conclusively demonstrate that halal tourism exerts a significant positive influence on both the welfare and the income of local communities in Makassar City. Statistical validation showed T-Statistics significantly exceeding the minimum threshold of 1.96, alongside strong P-Values of 0.000 (<0.05). This indicates a robust relationship. The implication is profound: the development of halal tourism contributes positively to the community’s economy, leading to higher social welfare, expanding local employment opportunities, and crucially strengthening the role of MSMEs (Micro, Small, and Medium Enterprises) as key drivers of regional economic growth.